Evaluation of native Zoysia japonica and Zoysia matrella accessions on river sediment and Alfisol media for turfgrass quality in Indonesia - RAHAYU RAHAYU; ZAINAL ISA ABIDIN; GANJAR HERDIANSYAH; SUPRIYADI SUPRIYADI; AGUSTIN AYU SAPUTRI (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Rahayu, Abidin ZI, Herdiansyah G, Supriyadi, Saputri AA. 2026. Evaluation of native Zoysia japonica and Zoysia matrella accessions on river sediment and Alfisol media for turfgrass quality in Indonesia. Biodiversitas 27 (6): d270601. https://doi.org/10.13057/biodiv/d270601. Native turfgrass species in Indonesia have considerable potential for landscape and sports field applications; however, comparative evaluations of different accessions under contrasting soil media remain limited. This study evaluated the turf quality performance of several native accessions of Zoysia japonica and Zoysia matrella grown in two soil types, river sediment and Alfisol. The experiment was conducted using a randomized complete block design with three replications. Turf performance was assessed using visual and functional quality parameters based on the National Turfgrass Evaluation Program (NTEP) scoring system. Data were analyzed using Analysis of Variance (ANOVA) followed by Duncan’s Multiple Range Test (DMRT) to determine significant differences among treatments. The results showed that soil media significantly influenced several turf quality traits. ANOVA revealed significant interactions between accession and growing media (p<0.05), indicating genotype-specific responses to soil conditions. In general, river sediment provided more favorable conditions for turf growth than Alfisol. Among the evaluated accessions, the Kopeng accession of Z. matrella showed the highest visual quality, with scores approximately 1.92% higher than Zeon on sediment and 48.78% higher on Alfisol. Compared with Zmeet, Kopeng also showed higher visual quality, reaching 44.71% on sediment and 46.47% on Alfisol. Overall, Z. matrella accessions showed higher visual quality, whereas Z. japonica tended to exhibit better functional traits under sediment conditions. These findings demonstrate that selected Indonesian Zoysia accessions possess high adaptability and competitive turf quality, supporting their potential as locally adapted alternatives to imported cultivars for sports fields and landscape applications. The study provides important baseline information for turfgrass management and breeding programs aimed at improving turf performance in Indonesian environments. Z. japonica accession in higher elevation showed better quality, while Z. matrella showed better quality in relatively lower elevation.